A specific selenium-chelating peptide isolated from the protein hydrolysate of Grifola frondosa. Issue 17 (9th March 2021) - Xiong, Yu; Chen, Zi-Hong; Zhang, Feng-Li; Yu, Zhi-Ying; Liu, Bin; Zhang, Chong; Zhao, Li-Na
Abstract : A selenium chelating peptide was isolated and purified from Grifola frondosa hydrolysate, which may be a promising selenium supplement. Abstract : Background : Grifola frondosa is a type of edible medicinal mushroom with abundant proteins. Selenium (Se) is an essential micronutrient for human. Many animal experiments and clinical studies had indicated that Se plays an important role in diverse physiologic actions. Most inorganic selenium compounds are toxic, and the lowest lethal dose is relatively small. Peptide-Se chelate can probably be dietary supplements in functional foods for humans with Se deficiency. Methods : In this study, a specific tripeptide Arg-Leu-Ala (RLA) with strong Se-chelating capacity was purified from Grifola frondosa through ultrafiltration, reversed-phase HPLC and gel filtration chromatography. The UV, SEM, XRD, 1 H NMR spectra are shown to provide more information about characterization of RLA-Se chelates. The bioavailability of RLA-Se chelate in Caco-2 cell line was investigated by using human colon cancer Caco-2 cells as model. iTRAQ comparative proteomics approach were used to identify the differentially expressed proteins. Results : The Se binding capacity of RLA was 84.47 ± 1.21 mg g −1 . The results of UV, X-ray diffraction (XRD), 1 H NMR and SEM structure analysis showed that the binding of selenium in the hydrolysate of Grifola frondosa protein was successful, and the amino and carboxyl groups of RLA were involved in the coordination of Se, which was the main site of chelation. The results of absorption of RLA-Se chelate in Caco-2 cells showed that RLA-Se chelate could be used as selenium supplement source. Using iTRAQ comparative proteomics approach, 40 proteins found significant. RLA-Se treatment had been demonstrated to present a higher accumulation of Se compared with control treatment and show an effective absorption by Caco-2 with the result that E3 protein performed up regulation. RLA-Se may play roles in cell cycle and apoptosis as an essential micronutrient. To sum up, our research results show that Grifola polypeptide-Se chelate is a promising multifunctional organic selenium product, which can be used as a new functional supplement for selenium deficiency.